Quantitative dynamic 18F-fluorodeoxyglucose positron emission tomography/computed tomography before autologous stem cell transplantation predicts survival in multiple myeloma: letters to the editor - Sachpekidis, Christos; Merz, Maximilian; Kopp-Schneider, Annette; Jauch, Anna; Raab, Marc-Steffen; Sauer, Sandra; Hillengaß, Jens; Goldschmidt, Hartmut; Dimitrakopoulou-Strauss, Antonia (Haematologica, 2019)
Although the presence of focal lesions in 18F-fluo-rodeoxygluocse (FDG) positron emission tomography (PET)/computed tomography (CT) is associated with adverse outcome in multiple myeloma, data on diffuse bone marrow infiltration are lacking. In the current prospective study we investigated the
Im Titel ist "18" hochgestellt
Gesehen am 14.04.2020